How Can Clinical Outcomes among Adolescents Living with HIV in Ethiopia be Improved? Healthcare Professionals' Perspectives. Issue 2 (3rd April 2022) - Jerene, Degu; Tiberg, Iren; Hallström, Inger
ABSTRACT: While successes in the prevention of mother-to-child transmission program are believed to lead to substantial reductions in new perinatal infections, new sexually acquired infections among the older adolescent group seem to fuel the HIV epidemic. That is why adolescents are the only age group in which an increase in new HIV infections was reported in the latest global HIV progress update. Increase in the number of perinatally HIV infected children growing to adolescence adds to this pool. However, there is limited evidence on the specific needs of adolescents in resource-limited settings. The objective of this study was to assess the experiences and suggestions of health-care providers regarding clinical services for adolescents living with HIV in Ethiopia. The study was conducted in two regions of Ethiopia. An inductive qualitative approach, including focus group interviews among health-care professionals working with adolescents living with HIV was conducted between November 2015 and March 2016. Fifteen health-care professionals participated in three focus group discussions. The interviews were analyzed using qualitative content analyses. The health-care professionals' experiences are described in three categories: Youth specific support needed; Manifold support from and within society ; and Adults' fear of stigma . This led to the main theme: To see what is needed but not always being able to give . The main theme described that the health-care professionals were aware that the adolescents had specific health-care needs which they were not able to fulfill. They were also aware of the adolescents' need and support from the society and from their family, but they were not in control of it. Adolescents living with HIV have unique care needs which need to be met through evidence-guided introduction of adolescent-friendly services. This study further substantiates earlier findings that poor adherence to treatment and appointment schedules remains a critical challenge that needs interventions.